The Impact of the Ecosystem on Health Literacy Among Rural Communities in Protected Areas: Protocol For a Mixed Methods Study - Nor Aziah Abd Kadir; Amirah Azzeri; Hafiz Jaafar; Mohd Iqbal Mohd Noor; Zurina Kefeli@ Zulkefli (JMIR Publications, 2024)
Indexed by WOS/Scopus/ERA